1920
DOI: 10.1093/aob/os-34.3.367
|View full text |Cite
|
Sign up to set email alerts
|

Field Studies of the Carbon Dioxide Absorption of Coco-nut Leaves

Abstract: FIG. r. The apparatus used in testing the carbon dioxide absorption by coconut , photographed from theSE. on May 28, at 5 p.m., during the test of leaf 4• FIG. 2. A photograph of the coconut tree used in testing the carbon dioxide absorption of coco-ni1t leaves at different ages. This was taken on the same day as Fig. I. The leaves are designated by numbers corresponding to those used in the text. McLEAN-CARBON DIOXIDE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

1928
1928
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…per hour in order to make them comparable with Lnndegardh's figures (1931). The assimilation/time curve is saddle-shaped, and similar in this respect to those descrihed hy McLean (1920) and Thoday (1910). This depression is due to partial closure of the stomates during the midday period, as shown by Maximov's field method.…”
Section: Carbon Assimilationsupporting
confidence: 61%
See 1 more Smart Citation
“…per hour in order to make them comparable with Lnndegardh's figures (1931). The assimilation/time curve is saddle-shaped, and similar in this respect to those descrihed hy McLean (1920) and Thoday (1910). This depression is due to partial closure of the stomates during the midday period, as shown by Maximov's field method.…”
Section: Carbon Assimilationsupporting
confidence: 61%
“…cms., was enclosed in a glass vessel by means of a divided cork, and air drawn over the leaf. Tn the first experiments the rate of tJow was 20 litres per hour, since this rate was found necessary hy McLean (1920) for sngar cane, hut was suhsequently reduced to ]0 litres per hour. No appreciable difference in carhon assimilation occurred at these two rates.…”
Section: Carbon Assimilationmentioning
confidence: 98%
“…The air interacted with the plant and was then passed through a solution, such as barium hydroxide, which absorbed CO 2 . The quantity of CO 2 absorbed by the solution was measured by titration and compared with the amount of CO 2 absorbed by a control solution to determine the rate of assimilation (McLean, 1920; Kostytschew et al ., 1928). Later, researchers modified this method by estimating absorbed CO 2 from the electrical resistance of the solution (Spoehr & McGee, 1924).…”
Section: Introductionmentioning
confidence: 99%
“…Since the optimal depth depends so closely on the light intensity, its (1920) and Yap (1920) have shown that the rate of photosynthesis of sugar-cane in the Philippines increases rapidly from about 7.30 a.m. to 9.30 a.m. and falls slightly in the middle of the day, rising again to a maximum about 5 p.m. An experiment was carried out to find the actual course of photosynthesis in the sea on a sunny day. Cages were sunk to 0, t, 1, 2, 3, 4, and 6 metres, and were changed every 3 hours over 24 hours.…”
mentioning
confidence: 99%